Investigating the effects and social harms of cyberspace on children - Jahantighi, Firouzeh (Journal of Psychosociological Research in Family and Culture, 2023)
The goal of the present study was to investigate the crisis that children face in the cyberspace. This research was conducted in a library manner and the findings indicate that in the last century and especially in the last decade, one of the topics that has been discussed a lot in various scientific societies and circles is the cyberspace topic. There are several reasons for this. Ease of use, attractiveness, comprehensiveness and variety of information, which can satisfy all ages and all tastes, are among the factors that have made Internet and cyberspace universal, and even children are highly exposed to them. Since the Internet connects different cultures and nations, it greatly impacts the formation or change of the identity of people, especially children, whose identity is being formed. In this research, we first examined the definitions of cyberspace and crisis and stated cyberspace versus identity, and then we examined the damages caused by cyberspace.